Outward Foreign Direct Investment and Domestic Investment : The Case of Developing Countries - Al-Sadiq, Ali (IMF Working Papers; Working Paper, 2013)
Over the past two decades, the growth rate of outward foreign direct investment (FDI) from developing and transition economies has increased significantly. Given the role of physical capital accumulation in determining the economic growth rate, it is important to assess how domestic investment responds to such outflows. This study empirically examines the effects of outward FDI on domestic investment in developing countries. Using data from 121 developing and transition economies over the period 1990-2010, the results suggest that FDI outflows negatively impact the rate of domestic investment.